Comparison of the use of traditional classroom drills and of online learning materials in the development of mathematical skills (2019)
The study quantitatively investigated the effectiveness of the use of online learning resources against the use of traditional classroom drills in the development of the mathematical skills of the student-participants. Through the conventional pre-test and post-test assessments approach, the researchers were able to show that both methods are equally efficient in developing the skills of the learners. Though none of the methods stood out to be better than the other, the study has shown that online learning resources can substitute for the use of the said drills and lead the learners to attain the same learning outcomes.
Keywords: Online learning; Classrooms; Virtual classrooms; Drills; Mathematical ability